Tunnelling: Evidence From Indonesia Stock Exchange - Nurazi, Ridwan; Santi , Fitri; Usman, Berto (Asian Academy of Management (AAM), 2015)
This study investigates the relationships between corporate governance variables and tunnelling activities in Indonesia. Using 2216 firm-year observations from 2005 to 2012, we find that several corporate governance variables contribute to explaining the phenomenon of tunnelling in Indonesia. The data reveal that approximately 276 firms had experienced expropriation in the form of tunnelling, particularly expropriation from majority to minority shareholders, which can be identified through the related party transaction. We find that firms with family and state ownership tend to experience tunnelling. This result is consistently revealed when we separate the data into eight industries. We document that the SINGLE ownership variable, which depicts family ownership, the STATE ownership variable, and the LEVERAGE variable have a positive influence on TUNNELING. In contrast, the institutional (INST) ownership variable has a negative influence on TUNNELING. However, BOARD_SIZE, OUTSIDERS, GROUP ownership, and BIG FIVE auditor variables have no significant effect on TUNNELING activities.